Evaluación del potencial del aprovechamiento del agua de lluvia en la facultad de Ecología – UNSM – T, Moyobamba – San Martín - Cruz Carranza, Gumber Josbal (2014)
The study of the use of rainwater: I annul faculty of ecology of St. Martín Tarapoto's National University UN-SAMARIUM T, it has the purpose to detennine the hydric offer generated by precipitation (rainwater) and consistent mind to analyze the possibilities of use ru1d sustainable use ofthe water resource. San Martin P.eru's, Ubicado's Sub-Region of the High May, Departamento in the Nor Orient ofthe Pemvian Amazonia, is a zone ofhigh precipitation (1720,9 mm), but of insufficient availability of water for population use, besides precipitation, in the survey area, has characteristics very told apart as to intensity, duration and frequency. Besides the increment of the student population is every year more than the previous one and he finds itself distributed between the different academic cycles of both academic schoo.ls and besides, the adminjstrative st:a,ff, teachers and among others. The purpose of the following project ís demonstrating the potentíal saving of the use of rainwater for institutional cases rural populations and traffic policemen. The sustentabilidad is one of the motives why the use of rainwater has become popular recently. It is a responsible way to design landscapes and gardens. The presence of the rainwater of the projects of use helps to limit the soil erosion, run~ffs atld the water pollution. A step toward the local self-sufficiency that reduces the need to be important is externa!- resources water not sustainable. Furthennore, the people get a concrete lesson about the use and the conservation of water, since he can see water clearly how much he produces the local climate.